Many-Valued logics and translations - D'Ottaviano, Ítala M. Loffredo [UNESP]; Feitosa, Hércules D. Araujo [UNESP] (Taylor & Francis, 1999)
This work presents the concepts of translation and conservative translation between logics. By using algebraic semantics we introduce several conservative translations involving the classical propositional calculus and the many-valued calculi of Post and Lukasiewicz.
Keywords: Algebraic semantics; Conservative translations; Lukasiewicz logics and algebras; Many-valued logics; Post logics and algebras; Translations